Flagellation and swimming motility of Thermoplasma acidophilum. - Black, F T (1979)
Electron microscopy of thin sections of Thermoplasma acidophilum confirmed previous observations of the absence of a typical cell wall in this organism. Negatively stained specimens revealed the almost consistent occurrence in both strains examined of monotrichously arranged flagella, about 9 micrometer long, which describe a sinuous curve with a wavelength of 1.5 to 2.0 micrometer and an amplitude of 0.33 to 0.59 micrometer. Motility of T. acidophilum could be demonstrated microscopically by microcinematography and macroscopically. The theoretical implications of the demonstration of functioning flagella in a wall-defective organism are discussed in the light of current theories of the mechanism of flagellar motility and from a taxonomic point of view.